Merebut Panggung Politik: Menelisik Partisipasi Perempuan Dalam Pemilu Legislatif di Kecamatan Payakumbuh Timur Tahun 2024 - Aperta Safatullah, Afdal; Chofa, Fery; Vahlepi, Muhmmad; Mulia Saputra, Ego; Hikmara, M. Abdi; Kholdaa, Maylaffnatisya (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The role of women in politics will be an interesting issue of discussion in the 2024 election, as legislation requires women to have 30% representation in parliament. The goal of this is to support pro-women policies in government. The purpose of this study is to examine the degree of female participation in the East Payakumbuh District 2024 parliamentary election. This study's outcome was a normative juridical approach to a juridical investigation. The secondary legal resources used as data sources included journals and a number of significant research findings pertaining to the topics covered in this study. Data analysis material is utilized to examine more closely the empirical and legal issues gleaned from a range of earlier researchers' research findings. Based on the data collected, this study contends that there are still various political parties with women's representation levels below 30%. These results highlight the necessity of taking more actions to improve women's representation in politics.